2023
DOI: 10.3390/life13102014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Maternal Hematological Disorders during Pregnancy and Neurological Development in Newborns: Mixed Cohort Study

Ebtisam Bakhsh,
Maan Alkhaldi,
Mostafa Shaban

Abstract: Maternal hematological disorders during pregnancy may pose a risk to the neurological development of newborns. To investigate the association between maternal hematological disorders during pregnancy and neurological outcomes in newborns, this mixed cohort study was conducted on 200 pregnant women diagnosed with hematological disorders during pregnancy. Some cases have been identified in the past who have completed the pregnancy in full, as well as cases in pregnancy. Currently, the children of all mothers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Although research remains limited on the vitamin D–dyslipidemia relationship, one of the proposed mechanisms is the regulation of vitamin D by various lipid metabolism genes involved in de novo cholesterol synthesis [ 38 ]. Low 25(OH)D levels have also been associated with higher levels of systemic inflammation, which can independently worsen blood lipids [ 39 , 40 ]. These data provide preliminary population-level evidence in a Saudi cohort that screening for and correcting vitamin D deficiency may be a valuable tool to prevent and manage dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although research remains limited on the vitamin D–dyslipidemia relationship, one of the proposed mechanisms is the regulation of vitamin D by various lipid metabolism genes involved in de novo cholesterol synthesis [ 38 ]. Low 25(OH)D levels have also been associated with higher levels of systemic inflammation, which can independently worsen blood lipids [ 39 , 40 ]. These data provide preliminary population-level evidence in a Saudi cohort that screening for and correcting vitamin D deficiency may be a valuable tool to prevent and manage dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Carapellotti et al (2022) demonstrated that a 12-week Dance for Parkinson's program improved symptoms of depression and discomfort while bolstering functional mobility in individuals with Parkinson's disease [49]. Morris et al (2023) verified the practicality of transitioning such dance programs online to enhance accessibility [50,108].…”
Section: Improving Overall Well-being and Quality Of Lifementioning
confidence: 99%
“…Furthermore, treatments that focus on NGFs have a considerable capacity to directly stimulate the renewal of the corneal epithelium and promote the regrowth of sensory nerves. This, in turn, helps in the production of tears and the stability of the ocular surface [ 99 ]. Furthermore, studies investigating the use of MMPIs indicate a possible approach to mitigate the breakdown of extracellular matrix, therefore improving the attachment and strength of epithelial cells [ 100 ].…”
Section: Reviewmentioning
confidence: 99%